PERFORMANCE IMPROVEMENT ANALYSIS OF THE 35,000 MSME FAMILY CHIK TOSEBAR DEVELOPMENT - Muhammad Nassa Ie; Muhammad Thoriq Al-Khairiri; Isra Jannah Yanti Zai; Khairil Anwar; Saharuddin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Statement from the Secretary of the Ministry of Cooperatives and SMEs Agus Muharam in the National Symposium on the Global Economy in an interview he said that MSMEs are the backbone and foundation of the people's economy, "so that if there is an economic crisis, because the MSMEs are strong, the economy will also remain strong. One of the SMEs that has been very developed from the start was the 35,000 Chik Tosebar family UMKM, which is in Lhokseumawe, to be precise, in Batuphat. Umkm is engaged in the clothing business. The emergence of a clothing business with a price of Rp. 35,000 has recently emerged in recent years. Data collection techniques can be carried out using several techniques, namely interviews, questionnaires, observation and a combination of the three techniques used by researchers. in collecting data using interviews (interview). According to Esterberg in Sugiyono (2019), an interview is a meeting of two people to exchange information and ideas through questions and answers, so that meaning can be constructed in a particular topic. In developing their business, shop owners use social media technology to introduce the products they market to consumers to make it easier and more efficient. The store does not only offer clothing products, in contrast to most 35,000 department stores in general, which only sell clothing. This store innovates products in its store by offering household products to consumers. Such as plates, glasses, drinking bottles and many others. The Chik Tosebar 35,000 family shop was very advanced and very developed at the time of its inception. Their development and progress can be seen in their product innovation and the turnover they get per month. Has a product quality that is very worth it with a maximum price of Rp. 35,000 The price is one that consumers really consider when buying